Respuesta :

Answer:

15

Step-by-step explanation:

Since we know x = 2 and z = 3x, let's find z by substituting the value for x into z:

z = 3(2) = 6

Now that we have the values of both x and z, we can substitute them into the expression and simplify:

x + 4z - 5 - 3x

= 2 + 4(6) - 5 - 3(2)

= 2 + 24 - 5 - 6

= 15

The equation gives 15 when we substitute x = 2 and z = 3x in the given equation.

What is substitution?

Substitution means replacing the variables (letters) in an algebraic expression with their numerical values.

According to the given question.

We have an equation

[tex]x+4z-5-3x[/tex]

To find the value of the above equation we have to substitute

[tex]x = 2 \ and \ z = 3x[/tex]  in [tex]x+4z-3x[/tex].

Therefore,

[tex]x+4z-5-3x \\= 2+4(3x)--53x\\=2+ 12x -5-3x\\=2+9x-5\\=2+9(2)-5\\=2+18-5\\=20-5\\=15[/tex]

Hence, the equation gives 15 when we substitute x = 2 and z = 3x in the given equation.

Find out more information about substitution here:

https://brainly.com/question/22340165

#SPJ2